2003
DOI: 10.1177/07419325030240050301
|View full text |Cite
|
Sign up to set email alerts
|

Status of and Trends in Academic Intervention Research for Students with Emotional Disturbance

Abstract: Recent research has examined overall trends in the experimental literature relating to students with emotional disturbance (ED). The current review was conducted to examine both the status of and trends in interventions designed to improve the academic functioning of students with ED. Fifty-five studies were included in the descriptive analysis, which spanned the years from 1975 to 2002. Descriptive dimensions of the research included participant demographics, settings, research designs, and dependent and inde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
84
0
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 84 publications
(89 citation statements)
references
References 72 publications
4
84
0
1
Order By: Relevance
“…Results were consistent with earlier investigations reporting subaverage academic performance among this group (Greenbaum et al 1996;Lane et al 2005a, b;Mooney et al 2003;Nelson et al 2004;Reid et al 2004;Trout et al 2003). Elementary and secondary group scores were well below the 25th percentile for reading, math, and written expression measures, with high magnitude differences (ES sm = −2.23) between the two groups on math performance.…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations
“…Results were consistent with earlier investigations reporting subaverage academic performance among this group (Greenbaum et al 1996;Lane et al 2005a, b;Mooney et al 2003;Nelson et al 2004;Reid et al 2004;Trout et al 2003). Elementary and secondary group scores were well below the 25th percentile for reading, math, and written expression measures, with high magnitude differences (ES sm = −2.23) between the two groups on math performance.…”
Section: Discussionsupporting
confidence: 81%
“…With respect to primary disability, 31 (73.81%) students had a classification label of emotional disturbance (ED) per the Individuals with Disabilities Education Improvement Act (IDEIA, 2004), 5 (11.90%) other health impaired-Attention Deficit Hyperactivity Disorder (ADHD; APA, 1994), 3(7.14%) learning disability (LD), 1 (2.38%) speech and language impairment, and 2 (4.76) mental retardation. The range of primary disability categories reported for this sample is comparable to other studies conducted in this setting, and all students had serious behavioral challenges that warranted support in a self-contained school for students with EBD (e.g., Barton-Arwood et al 2005;Lane et al 2005a;Mooney et al 2003;Reid et al 2004;Sutherland and Wehby 2001;.…”
Section: Participantssupporting
confidence: 61%
See 2 more Smart Citations
“…Unfortunately, few researchers have studied effective academic interventions for students with E/BD. A historical review of the academic intervention research conducted with these students showed that only 55 studies have been conducted over the past 30 years (Mooney, Epstein, Reid, & Nelson, 2003). Fot example, despite the severe reading problems faced by children with E/BD, scant research has examined the effects of reading interventions designed to improve the reading skills of children with E/BD.…”
Section: Discussionmentioning
confidence: 99%